Web-based engineering education critical design and effective tools - Russell, Donna L.; Haghi, A. K. 1958- (Engineering Science Reference, 2010)
Rapid advances in computer technology and the internet have created new opportunities for delivering instruction and revolutionizing the learning environment. This development has been accelerated by the significant reduction in cost of the Internet infrastructure and the easy accessibility of the World Wide Web. This book evaluates the usefulness of advanced learning systems in delivering instructions in a virtual academic environment for different engineering sectors. It aims at providing a deep probe into the most relevant issues in engineering education and digital learning and offers a survey of how digital engineering education has developed, where it stands now, how research in this area has progressed, and what the prospects are for the future
Includes bibliographical references
Keywords: Ingenieurwissenschaften; Engineering / Study and teaching (Higher); Web-based instruction; Educational Web sites; Distance education; Engineers / In-service training; Fernunterricht; Computerunterstützter Unterricht; World Wide Web; Aufsatzsammlung